Critical Appraisal of Management Practices in Nepalese Guava Orchards - Shrestha, AK (Journal of the Institute of Agriculture and Animal Science, 2005)
A survey was conducted to appraise the guava farming in Nepal with respect to the orchard management practices, cultivar status and major production constraints during July- December 2001. Guava plantation was extensively distributed throughout terai, inner terai and mid hill districts ranging in altitude from 115 masl to 1600 masl. Indian varieties dominated the guava plantation in Nepal although mix population of both improved and local cultivars was reported in majority of orchards. Preponderance of seedling origin guava plantation was noticed. The management practices were poor. Over 80% of the orchards received neither FYM nor chemical fertilizer. Similarly, more than 90% of the orchards were under rainfed condition. The peak period of flowering was reported during April/May followed by Feb/March that may extend up to June/July. As a consequence, the fruit availability period is mainly restricted to four months, i.e. July/ August to Oct/Nov. Most of the growers pointed out guava wilt as the main biotic constraint in guava production. The outcomes indicted the urgent need to adopt the effective control measures against the guava wilt malady to flourish guava enterprise in Nepal. Furthermore, off-season production of guava fruit has the great potential in Nepalese market. Key words: cultivar, guava wilt, orchard, Psidium guajava J. Inst. Agric. Anim. Sci. 26:127-133 (2005)